2021
DOI: 10.1002/vms3.443
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and reproductive function impairment of glyphosate‐based herbicide in male guinea pig (Cavia porcellus)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
4
8
0
Order By: Relevance
“…In our study, sperm motility was reduced at D5, D13 and D25 after RU exposure. These data are in good agreement with those observed in vivo in rats [39][40][41], mice [8], and pigs [42,43] and in vitro in humans [44,45]. In addition, the calcium and ATP concentrations in spermatozoa were significantly reduced in RU animals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, sperm motility was reduced at D5, D13 and D25 after RU exposure. These data are in good agreement with those observed in vivo in rats [39][40][41], mice [8], and pigs [42,43] and in vitro in humans [44,45]. In addition, the calcium and ATP concentrations in spermatozoa were significantly reduced in RU animals.…”
Section: Discussionsupporting
confidence: 90%
“…No impact on sperm concentration was recorded after dietary RU exposure, which contrasts with previous findings. Indeed, an exposure to G (500 mg/kg bw/d) for 5 weeks [50] or to RU (50 mg/kg bw/d) during the gestational period [9] or during adulthood in rats [40], mice [8], pigs [42] and in rabbits [51] led to a reduced sperm concentration. However, the effect of RU or G on the sperm concentration could be dependent on the species but also on the timing of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…both vertebrate and invertebrates [3][4][5], as well as in wildlife and aquatic species where this contaminant, alone or in formulation, induced oxidative stress an damage. These observations are raising concern about public health since GLY detected in the urine of humans [11].…”
Section: Metabolomic Characterization Of the Livermentioning
confidence: 99%
“…Limits for the presence of GLY in drinking water range from the highest levels in Australia (1000 µg/L) and USA (700 µg/L) to lower levels in Canada (280 µg/L) and Europe (0.1 µg/L) [ 2 ]. Despite the claim that GLY-based herbicides only target plant-specific enzymatic pathway, various studies demonstrated adverse effects of this contaminant in both vertebrate and invertebrates [ 3 , 4 , 5 ], as well as in wildlife and aquatic species [ 6 , 7 , 8 , 9 , 10 ], where this contaminant, alone or in formulation, induced oxidative stress and DNA damage. These observations are raising concern about public health since GLY can be detected in the urine of humans [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is defined as a physiological disturbance when the production of potentially destructive reactive oxygen species (ROS) exceeds the body's own natural antioxidant defense (Tremellen, 2008;Nimse and Pal, 2015;Mohammed et al, 2020). It has been associated with several chronic diseases such as diabetes, hypertension, inflammation, cancer, reproductive impairment in both humans and livestock (Nimse and Pal, 2015;Sevindik et al, 2018;Mutwedu et al, 2021) through DNA damage, lipid peroxidation, tissue injury and protein degradation (Unuigbe et al, 2014;Pehlivan et al, 2018). Research findings have shown that humans affected with such ailments often revert to use of synthetic antioxidants, which have been proven to quench or trap ROS (Nimse and Pal, 2015;Sevindik, 2019).…”
Section: Introductionmentioning
confidence: 99%